2021
DOI: 10.1182/bloodadvances.2020003679
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing-Based Monitoring of Circulating Tumor DNA Reveals Clonotypic Heterogeneity in Untreated PTCL

Abstract: Peripheral T-cell lymphomas (PTCL) have marked biologic and clinical heterogeneity, which confounds treatment decisions. Advances in circulating tumor DNA (ctDNA) assays employing next generation sequencing (NGS) has improved the detection of molecular relapse and driver mutations in diffuse large B-cell lymphoma, and highlight the potential utility of ctDNA across lymphomas. We investigated NGS-based monitoring of T-cell receptor (TCR) sequences in PTCL patients undergoing frontline treatment (NCT00001337). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…However, in a previous study with 20 patients, it was not possible to demonstrate an association between mutations and clinical parameters or survival [132]. Milkjovic et al used dPCR to detect TCR rearrangements in 34 patients with peripheral T cell lymphoma (PTCL), and reported that a median 2.6-log decrease in their ctDNA level after the first two cycles of treatment and that early clearance of ctDNA after cycle 2 was not associated with a statistically significant improvement in EFS (median (95% CI), 8.4 (0.1-NR) vs. 2.0 (0.1-NR) years; p = 0.32) or OS (median, 8.4 (0.3-NR) vs. 7.0 (0.5-NR) years; p = 0.44) [133].…”
Section: T Cell Lymphomasmentioning
confidence: 90%
See 1 more Smart Citation
“…However, in a previous study with 20 patients, it was not possible to demonstrate an association between mutations and clinical parameters or survival [132]. Milkjovic et al used dPCR to detect TCR rearrangements in 34 patients with peripheral T cell lymphoma (PTCL), and reported that a median 2.6-log decrease in their ctDNA level after the first two cycles of treatment and that early clearance of ctDNA after cycle 2 was not associated with a statistically significant improvement in EFS (median (95% CI), 8.4 (0.1-NR) vs. 2.0 (0.1-NR) years; p = 0.32) or OS (median, 8.4 (0.3-NR) vs. 7.0 (0.5-NR) years; p = 0.44) [133].…”
Section: T Cell Lymphomasmentioning
confidence: 90%
“…Additionally, Spina et al reported that a greater than 2-log reduction in cfDNA between diagnosis and after two chemotherapy courses was linked to a complete metabolic response and cure, but these studies have several limitations and more evidence is needed to incorporate liquid biopsies into the monitoring of MRD in lymphomas [133,137].…”
Section: Hodgkin Lymphomamentioning
confidence: 99%
“…However, in a previous study with 20 patients, it was not possible to demonstrate an association between mutations and the clinical parameters or survival [ 129 ]. Milkjovic et al used dPCR to detect TCR rearrangements in 34 patients with peripheral T-cell lymphomas (PTCL), and reported a median 2.6-log decrease in their ctDNA levels after the first two cycles of treatment, as well as the early clearance of ctDNA after cycle 2, were not associated with a statistically significant improvement in EFS (median (95% CI), 8.4 (0.1–NR) vs. 2.0 (0.1–NR) years; p = 0.32) or OS (median, 8.4 (0.3–NR) vs. 7.0 (0.5–NR) years; p = 0.44) [ 130 ].…”
Section: Lymphoid Malignanciesmentioning
confidence: 99%
“…Additionally, Spina et al reported that a two-log reduction in cfDNA, or greater, between the diagnosis and after the two chemotherapy courses, was linked to a complete metabolic response and cure. However, these studies have several limitations, and more evidence is needed to incorporate liquid biopsies into the monitoring of the MRD in lymphomas [ 130 , 134 ].…”
Section: Lymphoid Malignanciesmentioning
confidence: 99%
“…High levels of ctDNA pre-treatment correlate with advanced disease stage, and worse prognosis in many subtypes of lymphoma, including DLBCL [ 114 - 116 ] , FL [ 117 - 119 ] , and MCL [ 120 ] . Real-time monitoring of ctDNA level during therapy has been explored in a variety of lymphoma subtypes including DLBCL [ 114 ] , FL [ 119 ] , HL [ 121 ] , MCL [ 122 , 123 ] , and PTCL [ 124 ] , and preliminary studies demonstrate that changes in ctDNA can predict clinical outcomes including end of treatment response and risk of progression after completion of treatment. For example, a recent study demonstrated that monitoring of ctDNA improves early relapse detection after Axicabtagene Ciloleucel CAR T-cell therapy in DLBCL [ 125 ] .…”
Section: Prediction Of Response To Therapymentioning
confidence: 99%